(3fHPI GdYUQ aj CNHGQ edhc Hfi fUQs - (3eMeO Hf YHO Gddg Hf SYjO GdSdeGfj GddhTj GdCUd, GdZQfGWj GdCfOdSj, CHh YHO Gddg, GdTgjQ HdSGf GdOjf GHf GdNWjH,J (B776 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdeHOF GdeYjO CeG HYO agPG cJGH CPcQ ajg fHPg ef HYV JhGQjN eG hbY ai eOI GdCejQ CHj GdMSf Ydi Hf fUQ s
(3BNQgG (B:s
(3hcGf CeQ Gddg bOQkG ebOhQkG hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde JSdjekG cKjQkG s
(3HgG fXGe GdJYbjHIs
(3ai GdcJGH CMOGK hbYJ ai SfI (B891 (3SfI heGHYOgGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B235s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(28 / 1 (3O(B) s
Keywords: (3GdJGQjNs